WINNING STRATEGY: CONTINUOUS EVALUATION AS THE KEY TO SUCCESS MADRASAH EDUCATION MANAGEMENT - Basri, Moh Hasan; Najiburrohman, Najiburrohman; Faiz, Faiz; Sahidah, Ahmad; Firdaus, Sulton (PROCEEDING OF INTERNATIONAL CONFERENCE ON EDUCATION, SOCIETY AND HUMANITY, 2024)
This research aims to analyze and explore the role of superior strategies in improving the educational management of Madrasah Ibtidaiyah (MI) Hasanuddin in Satrean Maron Probolinggo. The main focus of the research is continuous evaluation as a critical element that can stimulate progress in educational management at MI Hasanuddin. This research analyzes sustainable evaluation practices implemented and involves a contextual approach to local dynamics in Satrean Maron Probolinggo. This research uses a qualitative case study type method by conducting research aimed at describing problems and analyzing the issues that occur. Researchers collected data through several stages, such as observation and direct observation at the research site. Interview interviewing several informants at the research location. Observation, visiting research locations. Documentation study, analyzing documents related to research. The research was conducted at the Madrasah Ibtidaiyah (MI) Hasanuddin institution in Satrean Maron Probolinggo. Based on the results of the research undertaken show that several innovations have been adopted by MI Tarbiyatul Islam, including (1) MI Hasanuddin in Satrean Maron has become a research center as a representative of Madrasah Ibtidaiyah in that environment. The continuous evaluation method here is an assessment tool and a dynamic process that focuses on continuous monitoring and improvement that is responsive to change. This aims to achieve adaptive and quality-oriented educational management. (2) Implementation of continuous evaluation as the main instrument in improving madrasa education management. In addition, this research explores the potential of technology integration as a support for continuous evaluation processes.